Analisis VECM Hubungan Tingkat Inflasi, Pengeluaran Pemerintah, Dan Ekspor Terhadap Pertumbuhan Ekonomi di Indonesia - Moh Reza Noer Irvansyah (CV. Ulil Albab Corp, 2024)
Economic conditions from the monetary crisis to the new era in 2022 indicate that the economy in Indonesia is still at a medium level. Sectors that play a role in increasing economic growth such as international trade activity are supporting economic growth. So this study was conducted to determine whether there is a relationship between Inflation, Exports, Government Expenditure and Economic Growth in Indonesia. This study uses a quantitative approach using VECM analysis. This study uses secondary data from the World Bank. Based on this research, the results show that all variables affect each other both in the short and long term, with different levels of significance.